Respuesta :

Solution:

[tex]-0.5[/tex]

Steps:

[tex](4x - 1) - 3x = - (x + 2)[/tex]

Start with the left side and combine like terms

[tex]4x-1-3x=-(x+2)\\[/tex]

Combine [tex]4x[/tex] and [tex]-3x[/tex]. After doing this, you would have [tex]x[/tex] because 4-3 = 1

[tex]x-1 =-(x+2)[/tex]

Then, you can distribute the negative on the right side

[tex]-(x+2) = -(x)+-(2) = -x-2[/tex]

You would end up with

[tex]x-1=-x-2[/tex]

Add x to each side.

[tex]2x-1=-2[/tex]

Add 1 to each side

[tex]2x=-1[/tex]

Divide each side by 2 to simplify.

[tex]x=-1/2\\x = -0.5[/tex]